LAWFUL LIMITATION OF THE RIGHT TO WORK IN THE CONTEXT OF THE FRIES JUDGMENT OF THE COURT OF JUSTICE OF THE EUROPEAN UNION - Zaccaria, Márton Leó (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The present paper examines two main recent issues of the social policy of the European Union (EU). The legal basis of the analysis includes some of the most significant areas of labour law and social law in the European Union. The Court of Justice of the European Union (CJEU) recently has decided some cases regarding the fundamental rights of workers based on the Charter of Fundamental Rights of the European Union and these judgments can mostly raise several concerns related to the interpretation of these rights. It is important that the CJEU has such judgments and it is of high importance that fundamental social rights are considered in these cases. Although, the subject of this paper is the judgment C-190/16, the reasoning and conclusions on the following pages apply to not only this case but also in general regarding the right to work and the prohibition of age discrimination. The lawful or unlawful limitation of these fundamental rights are highlighted because nowadays they mean more than meets the eye, keeping in mind the labour market challenges in the European Union. Consequently, the CJEU has come to important conclusions that have to be interpreted in the context of the recent changes of the social policy of the EU. The paper contains a short outline of the national case and the judgment of the CJEU. The main part of the paper consists of a merit analysis with comments and criticism concerning the limitation to the two emphasised fundamental rights. Conclusions are also included highlighting the importance of the right to work and equal employment in the social and employment policy of the European Union focusing mainly on the freedom to choose an occupation.